Dasar-Dasar Kebijakan Kurikulum di Madrasah Ibtidaiyah - M. Bustanul Ulum; Mar’atus Sholihah (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2020)
Curriculum policies that change frequently are influenced by one basis that dominates and affects other policy bases. Political basis is the main key in curriculum development in madrasah ibtidaiyah (elementary school) in order to succeed its education process. The basic curriculum policies in madrasah ibtidaiyah does not only consist of philosophical, psychological, sociological, scientific and technological developments, organizational, and political, but are also closely related to the basis of religion as part of an institution that teaches religious education through formal education. This religious basis is important to be embedded in madrasah ibtidaiyah curriculum as an effort to answer modern problems regarding to the behavior of children and adolescents, especially children. The provision of a religious foundation carried out since childhood is believed to be able to strengthen the formation of good behavior (good morals), as has been implemented by Islamic basic education institutions (madrasah ibtidaiyah) so far by teaching religious subjects separately using the broad fields curriculum design. Kebijakan kurikulum yang sering berubah dipengaruhi oleh salah satu dasar yang mendominasi dan mempengaruhi dasar kebijakan lain. Dasar politik menjadi kunci utama dalam pengembangan kurikulum di madrasah ibtidaiyah untuk menyukseskan proses pendidikan jenjang dasar. Dasar kebijakan kurikulum di madrasah ibtidaiyah tidak hanya terdiri dari dasar filosofis, psikologis, sosiologis, perkembangan IPTEK, organisatoris, dan politik, namun juga sangat lekat dengan dasar agama sebagai bagian dari lembaga yang mengajarkan pendidikan agama melalui pendidikan formal. Dasar agama ini menjadi penting untuk disematkan dalam kurikulum madrasah ibtidaiyah sebagai upaya menjawab permasalahan moderen tentang perilaku anak dan remaja, terutama anak. Pemberian fondasi agama yang dilakukan sejak masa anak-anak dipercayai mampu memperkuat pembentukan perilaku baik (akhlak baik), seperti yang telah diimplementasikan oleh lembaga pendidikan dasar Islam (madrasah ibtidaiyah) selama ini dengan mengajarkan mata pelajaran-mata pelajaran agama secara terpisah dengan menggunakan model the broad fields curriculum design.